The Codification of Hadith during the Era of Umar bin Abdul Aziz: Methodological Transformation and Its Impact on the Development of Hadith Studies - Ahmad Maigari Dutsinma (Walidem Institute and Publishing (WIP), 2025)
Objective: This study explores the pivotal role of Umar Ibn Abdulaziz (may Allah have mercy on him), the eighth Umayyad Caliph, in initiating the official compilation of Hadith. Recognized for his piety and administrative reforms, his efforts to preserve the Sunnah marked a transformative phase in Islamic intellectual history. The primary objective of this research is to analyze the motivations, methodologies, and impacts of his directive to collect and document the sayings and practices of Prophet Muhammad (peace be upon him). Theoretical Framework: The theoretical framework of this study is grounded in the principles of Islamic historiography and the science of Hadith, emphasizing the role of codification in religious preservation. Additionally, it adopts an epistemological approach to analyze the transmission and authentication of Hadith. Literature Review: The literature review explores previous research on Hadith compilation, particularly examining the works of early Hadith scholars such as Imam Malik, Al-Bukhari, and Muslim, whose collections were influenced by Umar Ibn Abdulaziz’s initiative. Methods: This study employs a qualitative historical research method, analyzing primary and secondary sources, including classical Hadith literature, historical chronicles, and contemporary scholarly discussions. By examining original edicts and narrations regarding Umar Ibn Abdulaziz’s policies, the study reconstructs the intellectual and political context of the first formal Hadith compilation. Results: Findings reveal that Umar Ibn Abdulaziz’s directive significantly mitigated the risks of Hadith distortion and loss, providing a systematic foundation for later Hadith scholars. His initiative institutionalized the Hadith collection, inspiring subsequent scholars to develop rigorous methodologies for authentication and classification. Implications: The study further highlights the implications of his codification efforts in shaping the framework of Islamic jurisprudence and Hadith studies. Novelty: The novelty of this research lies in its detailed analysis of the methodological transformation introduced during Umar Ibn Abdulaziz’s reign and its long-term impact on Islamic scholarship. By bridging historical narratives with modern epistemological perspectives, this study contributes to a deeper understanding of the development of Hadith sciences and Islamic legal thought.